The Correlation of Knowledge Level About Exclusive Mother’s Milk with Mother’s Milk Deliverance To The Baby - Ina Kuswanti (LPPM STIKES Guna Bangsa Yogyakarta, 2017)
Background: The giving  of exclusive mother’s milk was recommended for the baby until aged 6 months, because the mother’s milk contained a full nutrients to grow and development for the baby. The successful in giving exclusive mother’s milk was influenced by the mother’s knowledge about the exclusive mother’s milk. The data obtained also shownd that Danurejan 1 public healt was the lowest in exclusive breastfeeding gift that is 12,31%. Results of interviews with mothers of babies 6-12 months found mother’s who did not breastfeed exclusive of 7 people.